2017
DOI: 10.1002/2017jg003785
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Sulfide in Shallow Aquatic Ecosystem Sediments: An Analysis of the Roles of Sulfate, Organic Carbon, and Iron and Feedback Constraints Using Structural Equation Modeling

Abstract: The generation of elevated concentrations of sulfide in sediment pore waters that are toxic to rooted macrophytes is problematic in both marine and freshwaters. In marine waters, biogeochemical conditions that lead to toxic levels of sulfide generally relate to factors that affect oxygen dynamics or the sediment iron concentration. In freshwaters, increases in surface water sulfate have been implicated in decline of Zizania palustris (wild rice), which is important in wetlands across the Great Lakes region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…The relationship between surface water SO 4 and Hg methylation can be strongly affected by site‐specific conditions. Because of the variable conversion of SO 4 in surface water to sulfide in pore water—primarily due to differences in OM and Fe availability (Pollman et al, )—researchers have found a broad range in the SO 4 concentration associated with maximum efficiency of Hg methylation. For example, Orem et al () observed that two different areas in the Everglades Protection Area had peak surface water MeHg concentrations at SO 4 concentrations of 2 and 10–15 mg L −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between surface water SO 4 and Hg methylation can be strongly affected by site‐specific conditions. Because of the variable conversion of SO 4 in surface water to sulfide in pore water—primarily due to differences in OM and Fe availability (Pollman et al, )—researchers have found a broad range in the SO 4 concentration associated with maximum efficiency of Hg methylation. For example, Orem et al () observed that two different areas in the Everglades Protection Area had peak surface water MeHg concentrations at SO 4 concentrations of 2 and 10–15 mg L −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The quantitative estimates of internal loading of N, P, and Hg in response to MSR‐induced carbon mineralization may have been underestimated by the measured surface water concentrations, given that significant loss of these constituents to periphyton may have occurred. In addition, THg was filtered prior to analysis, which would have removed any Hg associated with phytoplankton or other suspended particles. Lack of either overland or groundwater loading of particulate and dissolved material, specifically iron: the availability of iron in sediment is a primary controller of the fate of MSR‐produced sulfide (Pollman et al, ). In natural aquatic systems, iron would be supplied at a relatively constant rate from the system's watershed over the long term, although varying in magnitude from watershed to watershed (Maranger et al, ; Winter, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three subsets of the field data were identified for the analyses reported here. A subset that consists of all of the samples from natural waterbodies (excluding the cultivated paddies) with virtually complete analyses (surface water, pore water, and bulk sediment; n = 194) was termed for internal purposes Class D. Pollman et al () used Class D to develop a structural equation model to elucidate key variables that govern the concentration of sulfide in sediment pore water. A second subset, Class S, of 51 samples from 7 stream and 8 lake sites was each sampled 3 to 5 times from 27 May to 19 September 2013, to provide a data set to assess seasonality in variables.…”
Section: Methodsmentioning
confidence: 99%
“…We report here on a multiyear field survey that was part of a larger study (Myrbo et al, ; Pastor et al, ; Pollman et al, ) designed to reevaluate the 10 mg L −1 SO 4 standard by testing potential mechanisms by which SO 4 might be harmful to wild rice. SO 4 is a relatively nontoxic and unreactive compound under aerobic conditions.…”
Section: Introductionmentioning
confidence: 99%